Web-Based Payroll Data Security Application Using the AES Cipher Method at the Mangga Dua Store Kebumen - Pandu Cahyo Sukoco; Afwan Anggara (University of Technology Yogyakarta, 2022)
Mangga Dua Store is a shop that is engaged in selling clothes, pants, and other products. In processing salary data, Mangga Dua Store employees only process data in the form of text files in Microsoft Excel without any file protection which causes misuse of data by unauthorized people. To solve this problem, data protection is needed using a method to encrypt employee salary data. In a study conducted to protect employee salary data using the AES 128 Cipher Method. This research resulted in a Web-Based Payroll Data Security Application Using the AES 128 Cipher Method by performing encryption and decryption to protect employee salary data. Based on the results of research and discussions that have been carried out, it shows that with the Data Security Application Using the Aes Cipher Method 128 employee salary data at the Mangga Dua Store can be encrypted and decrypted. So that it can avoid any misuse or manipulation of data that can be done by unauthorized people which can result in losses to the Mangga Dua Store.